Magnetic molecularly imprinted polymer capable of selectively adsorbing ibuprofen and preparation method of magnetic molecularly imprinted polymer
By preparing magnetic molecular imprinted polymers (MMIPs) of Fe3O4@SiO2-C=C nanoparticle carriers, the problems of insufficient selectivity and adsorption capacity of existing adsorbents when removing ibuprofen in water are solved, and efficient and selective removal of ibuprofen in water is achieved, and good performance is shown in solid phase extraction.
Patent Information
- Application Number
- CN202510423074.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-06-03
AI Technical Summary
Existing adsorbents lack selectivity, high adsorption capacity and reusability when removing ibuprofen in water, and traditional pollutant removal methods have problems such as non-selectivity and prone to secondary contamination.
Magnetic molecular imprinted polymers (MMIPs) were prepared by using Fe3O4@SiO2-C=C nanoparticles as carrier, ibuprofen as template molecules, 3-aminopropyltriethoxysilane (APTES) as functional monomers, and tetraethoxysilane (TEOS) as crosslinking agents, and their adsorption performance was evaluated by adsorption isotherms, adsorption kinetics and selective adsorption.
Efficient and selective adsorption and removal of ibuprofen in water is achieved, with high adsorption capacity (Qm = 68.18 mg/g) and imprinting factor (IF = 1.70), and exhibits good recovery and precision in solid phase extraction.
Smart Images

Figure CN120082092A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnetic molecularly imprinted polymers, and is a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen, its preparation method and application. Background Art
[0002] At present, various adsorbents have been used to remove ibuprofen from wastewater, such as activated carbon, magnetic hybrid nanomaterials and metal-organic frameworks.
[0003] For example, Olugbenga Solomon Bello et al. in "Sustainable Chemistry and Pharmacy 13(2019)100151" used bean husks modified with orthophosphoric acid to adsorb ibuprofen in aqueous solution, and the maximum adsorption capacity at 50 °C was 50.0 mg / g.
[0004] Guangyu Wu et al. in "Talanta 195(2019)390–400" used rapeseed straw biomass fiber / β-CD / Fe 3 O 4 to adsorb ibuprofen, and the maximum adsorption capacity was 48.29 mg / g. Although these adsorbents have certain adsorption properties for IBP, most adsorbents lack good selectivity, high adsorption capacity and reusability for IBP.
[0005] Molecular imprinting technology (MIT) provides a method for selective recognition and adsorption. Molecularly imprinted polymers (MIPs) prepared by molecular imprinting technology can specifically recognize analytes in complex samples. The preparation method of magnetic molecularly imprinted polymers (MMIPs) is to load a molecular imprinting layer on the surface of magnetic nanomaterials to form a material with both magnetic response and selective recognition. MMIPs can promote rapid separation and solve the limitations of traditional molecularly imprinted polymers, such as high mass transfer resistance and few effective imprinting sites.
[0006] Dongliang Xie et al. in "Journal of Materials Science & Technology 211(2025)159–170" used Fe 3 O 4 -e / KH570 as a carrier and dithiophospholipid as a template molecule to construct MMIPs. The adsorption capacity in lemon peel samples reached 20.25 mg / g, and the recovery rate was 91.20% to 94.16%, achieving excellent adsorption performance and specific recognition.
[0007] In "INTERNATIONAL JOURNAL OF ENVIRONMENTAL ANALYTICAL CHEMISTRY 2024, VOL.104, NO.19, 7699–7721", Ahmad Reza Bagheri et al. synthesized a dual-template molecularly imprinted polymer (TiO 2 -MIP) based on TiO 2 nanoparticles by surface molecular imprinting method to achieve the selective removal of ibuprofen. The synthesized TiO 2 -MIP nanocomposite had an adsorption capacity of 4.38 mg / g for ibuprofen.
[0008] In "J Sol-Gel Sci Technol (2013) 66:59–67", Ling Zhou et al. prepared a molecularly imprinted polymer (MIP) by a semi-covalent imprinting method using the non-steroidal anti-inflammatory drug ibuprofen as a template through a sol-gel process. The results of the equilibrium binding experiment showed that the MIP had a good adsorption capacity of 35.2 mg / g for ibuprofen.
[0009] It can be seen that MMIPs have a high specific recognition ability, and their imprinting factor (IF) is 3.49. Due to the specificity of MMIPs, MMIPs have a wide range of applications in solid-phase extraction (SPE), sensors, catalysts, etc. The application of MMIPs in solid-phase extraction not only solves the problem of poor selectivity of traditional stationary phases but also has higher utilization value.
[0010] Due to the widespread use and incorrect disposal of ibuprofen (abbreviated as IBP), its concentration in the environment is relatively high. At present, many important technologies have been applied to remove IBP in water. However, traditional pollutant removal methods (such as biodegradation, ozonation, photodegradation, etc.) usually have problems such as non-selectivity and easy secondary pollution. Therefore, the development of customized materials with high selectivity, specificity, and long-term stability, as well as efficient, environmentally friendly, and economical water purification technologies, has become the focus of current research. The demand for selective removal of ibuprofen is urgent, but there is less research on this part in the field of molecular imprinting. Summary of the Invention
[0011] The present invention provides a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen, its preparation method, and application, overcoming the above-mentioned deficiencies of the prior art. The structure of the magnetic molecularly imprinted polymer was comprehensively characterized, and its adsorption performance was evaluated by adsorption isotherms, adsorption kinetics, and selective adsorption. The results showed that the magnetic molecularly imprinted polymer is an effective adsorbent for removing and detecting IBP in water.
[0012] One of the technical solutions of the present invention is achieved by the following measures: A preparation method of a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen is carried out according to the following steps:
[0013] S1, prepare Fe 3 O 4 nanoparticles;
[0014] S2, prepare Fe 3 O 4 @SiO 2 ;
[0015] S3, prepare Fe 3 O 4 @SiO 2 -C=C nanoparticles;
[0016] S4, prepare a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen.
[0017] The following is a further optimization or / and improvement of one of the above-mentioned invention technical solutions:
[0018] In the above step S1, the specific process of preparing Fe 3 O 4 nanoparticles includes:
[0019] S11, dissolve the required amount of FeCl 3 -6H 2 O in ethylene glycol, then add the required amount of NaAc and PEG, and stir evenly to obtain a first mixture. Among them, 2.025 g of FeCl 3 -6H 2 O is dissolved in every 60 mL of ethylene glycol, and 5.50 g of NaAc and 1.50 g of PEG are added to every 2.025 g of FeCl 3 -6H 2 O;
[0020] S12, calcine the first mixture, and wash the obtained product with ultrapure water and ethanol alternately to remove impurities, and then vacuum dry to obtain Fe 3 O 4 nanoparticles, where the calcination temperature is 180 °C to 220 °C, the calcination time is 7.5 h to 8.5 h, the vacuum drying temperature is 55 °C to 65 °C, and the vacuum drying time is 7.5 h to 8.5 h.
[0021] In the above step S2, the specific process of preparing Fe 3 O 4 @SiO 2 includes:
[0022] S21. Disperse the required amount of Fe 3 O 4 nanoparticles prepared in step S1 in a mixed solution of ethanol and ultrapure water to obtain a first mixed solution;
[0023] S22. Add the required amounts of ammonia water and TEOS to the first mixed solution, mix them, and then perform vacuum drying to obtain Fe 3 O 4 @SiO 2 .
[0024] In the above step S21, 0.2 g of Fe3O4 nanoparticles are dispersed in every 125 mL of the mixed solution, where the volume ratio of ethanol to ultrapure water in the mixed solution is 4:1.
[0025] In the above step S22, 1.8 mL of ammonia water and 0.6 mL of TEOS are added to every 0.2 g of Fe 3 O 4 nanoparticles. The vacuum drying temperature is 55 °C to 65 °C, and the vacuum drying time is 7.5 h to 8.5 h.
[0026] In the above step S3, the specific process for preparing Fe 3 O 4 @SiO 2 -C═C nanoparticles includes:
[0027] S31. Disperse the required amount of Fe 3 O 4 @SiO 2 in a mixed solution of double-distilled water and acetic acid to obtain a second mixed solution;
[0028] S32. Add the required amount of MPS to the second mixed solution, mix and stir evenly, and then perform vacuum drying to obtain Fe 3 O 4 @SiO 2 -C═C nanoparticles.
[0029] In the above step S31, 0.2 g of Fe 3 O 4 @SiO 2 is dispersed in every 120 mL of the mixed solution, where the volume ratio of double-distilled water to acetic acid in the mixed solution is 9:1.
[0030] In the above step S32, 0.6 mL of MPS is added to every 0.2 g of Fe 3 O 4 @SiO 2 . The stirring time is 5.5 h to 6.5 h, the vacuum drying temperature is 55 °C to 65 °C, and the vacuum drying time is 7.5 h to 8.5 h.
[0031] In the above step S4, the specific process for preparing the magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen includes:
[0032] S41, Dissolve the required amount of IBP in methanol, and then add the functional monomer APTES. After mixing and stirring, a prepolymer is obtained;
[0033] S42, Add the required amounts of ammonia water and crosslinking agent TEOS to the prepolymer, and after mixing and stirring, a second mixture is obtained;
[0034] S43, Add the required amount of Fe 3 O 4 @SiO 2 -C═C nanoparticles prepared in step S3 to the second mixture. After ultrasonic dispersion, a third mixture is obtained;
[0035] S44, After stirring the third mixture, wash it with an eluent and then vacuum dry it to obtain the magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen.
[0036] In the above step S41, 0.1053 g of IBP is dissolved in every 30 mL of methanol, and 0.45 mL of APTES is added to every 0.1053 g of IBP.
[0037] In the above step S42, every 1 mL of ammonia water is mixed with 3.75 mL of TEOS, and the stirring time is 20 minutes to 40 minutes.
[0038] In the above step S43, the added amount of Fe 3 O 4 @SiO 2 -C═C nanoparticles is 0.2 g.
[0039] In the above step S44, the stirring time is 50 minutes to 70 minutes, the eluent is a mixed solution composed of methanol and acetic acid with a volume ratio of 9:1, and it is washed until there is no ultraviolet-visible light adsorption at a wavelength of 264 nm in the eluent. The vacuum drying temperature is 55 °C to 65 °C, and the vacuum drying time is 7.5 h to 8.5 h.
[0040] The second technical solution of the present invention is achieved by the following measures: A magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen obtained by a preparation method of a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen.
[0041] The third technical solution of the present invention is achieved by the following measures: An application of a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen in selectively adsorbing ibuprofen.
[0042] The present invention uses Fe 3 O4 @SiO 2 Using -C=C nanoparticles as carriers, IBP as the template molecule, APTES as the functional monomer, and TEOS as the crosslinking agent, a magnetic molecularly imprinted polymer for adsorbing IBP was prepared. Its structure was comprehensively characterized, and its adsorption performance was evaluated by adsorption isotherms, adsorption kinetics, and selective adsorption. The results showed that the magnetic molecularly imprinted polymer is an effective adsorbent for removing and detecting IBP in water. Brief Description of the Drawings
[0043] Appendix Figure 1 This is the adsorption kinetics curve graph of IBP-MMIPs and MNIPs in the present invention.
[0044] Appendix Figure 2 This is the statistical graph of the adsorption selectivity of MMIPs and MNIPs for IBP relative to CA and SA in the present invention. Detailed Embodiments
[0045] The present invention is not limited by the following embodiments, and the specific implementation manners can be determined according to the technical solutions of the present invention and the actual situation. Various chemical reagents and chemical supplies mentioned in the present invention are well-known and commonly used chemical reagents and chemical supplies in the prior art unless otherwise specified.
[0046] The present invention will be further described below in conjunction with embodiments:
[0047] Example 1: The preparation method of the magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen is carried out according to the following steps:
[0048] S1, prepare Fe 3 O 4 nanoparticles;
[0049] S2, prepare Fe 3 O 4 @SiO 2 ;
[0050] S3, prepare Fe 3 O 4 @SiO 2 -C=C nanoparticles;
[0051] S4, prepare the magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen.
[0052] The present invention uses Fe 3 O 4 @SiO 2-C=C as the carrier, ibuprofen (hereinafter referred to as IBP for short) as the template molecule, 3-aminopropyltriethoxysilane (hereinafter referred to as APTES for short) as the functional monomer, and tetraethoxysilane (hereinafter referred to as TEOS for short) as the crosslinking agent were used to prepare magnetic molecularly imprinted polymers (hereinafter referred to as MMIPs for short) for the selective adsorption of ibuprofen. The structure of MMIPs was comprehensively characterized, and their adsorption performance was evaluated by adsorption isotherms, adsorption kinetics, and selective adsorption. The results showed that MMIPs had a high adsorption capacity (Q m = 68.18 mg / g) and imprinting factor (IF = 1.70). Finally, MMIPs were used as solid-phase extraction (SPE) packing materials to concentrate and detect IBP in water. This method had a good detection limit (0.11 μg / mL), stable recovery rates (85.60% to 96.40%), and good precision (intra-day precision was 2.95% to 4.23%, and inter-day precision was 3.26% to 5.61%). Therefore, these results indicated that MMIPs were effective adsorbents for removing and detecting IBP in water.
[0053] Example 2: As an optimization of the above example, in step S1, the specific process of preparing Fe 3 O 4 nanoparticles included:
[0054] S11, Dissolve the required amount of FeCl 3 -6H 2 O in ethylene glycol, then add the required amount of NaAc and PEG, and stir evenly to obtain the first mixture. Among them, 2.025 g of FeCl 3 -6H 2 O was dissolved in every 60 mL of ethylene glycol, and 5.50 g of NaAc and 1.50 g of PEG were added to every 2.025 g of FeCl 3 -6H 2 O;
[0055] S12, Calcinate the first mixture, and the obtained product was washed alternately with ultrapure water and ethanol to remove impurities and then dried in vacuum to obtain Fe 3 O 4 nanoparticles, where the calcination temperature was 180 °C to 220 °C, the calcination time was 7.5 h to 8.5 h, the vacuum drying temperature was 55 °C to 65 °C, and the vacuum drying time was 7.5 h to 8.5 h.
[0056] Example 3: As an optimization of the above example, in step S2, the specific process of preparing Fe 3 O 4 @SiO 2 included:
[0057] S21. Disperse the required amount of Fe 3 O 4 nanoparticles prepared in step S1 in a mixed solution of ethanol and ultrapure water to obtain a first mixed solution;
[0058] S22. Add the required amounts of ammonia water and TEOS to the first mixed solution, mix them, and then conduct vacuum drying to obtain Fe 3 O 4 @SiO 2 .
[0059] Example 4: As an optimization of the above example, in step S21, disperse 0.2 g of Fe 3 O 4 nanoparticles in every 125 mL of the mixed solution, where the volume ratio of ethanol to ultrapure water in the mixed solution is 4:1.
[0060] Example 5: As an optimization of the above example, in step S22, add 1.8 mL of ammonia water and 0.6 mL of TEOS to every 0.2 g of Fe 3 O 4 nanoparticles, the vacuum drying temperature is 55 °C to 65 °C, and the vacuum drying time is 7.5 h to 8.5 h.
[0061] Example 6: As an optimization of the above example, in step S3, the specific process for preparing Fe 3 O 4 @SiO 2 -C═C nanoparticles includes:
[0062] S31. Disperse the required amount of Fe 3 O 4 @SiO 2 in a mixed solution of double-distilled water and acetic acid to obtain a second mixed solution;
[0063] S32. Add the required amount of MPS to the second mixed solution, mix and stir evenly, and then conduct vacuum drying to obtain Fe 3 O 4 @SiO 2 -C═C nanoparticles.
[0064] Example 7: As an optimization of the above example, in step S31, disperse 0.2 g of Fe 3 O 4 @SiO 2 in every 120 mL of the mixed solution, where the volume ratio of double-distilled water to acetic acid in the mixed solution is 9:1.
[0065] Example 8: As an optimization of the above example, in step S32, for every 0.2 g of Fe 3 O4 @SiO 2 Add 0.6 mL of MPS, stir for 5.5 h to 6.5 h, vacuum dry at 55 °C to 65 °C, and vacuum dry for 7.5 h to 8.5 h.
[0066] Example 9: As an optimization of the above example, in step S4, the specific process for preparing the magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen includes:
[0067] S41, Dissolve the required amount of IBP in methanol, then add the functional monomer APTES, and after mixing and stirring, obtain a prepolymer;
[0068] S42, Add the required amount of ammonia water and the cross-linking agent TEOS to the prepolymer, and after mixing and stirring, obtain a second mixture;
[0069] S43, Add the required amount of Fe 3 O 4 @SiO 2 -C=C nanoparticles, and after ultrasonic dispersion, obtain a third mixture;
[0070] S44, After stirring the third mixture, wash it with an eluent and then vacuum dry it to obtain the magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen.
[0071] Example 10: As an optimization of the above example, in step S41, dissolve 0.1053 g of IBP in every 30 mL of methanol, and add 0.45 mL of APTES to every 0.1053 g of IBP.
[0072] Example 11: As an optimization of the above example, in step S42, mix every 1 mL of ammonia water and 3.75 mL of TEOS, and stir for 20 minutes to 40 minutes.
[0073] Example 12: As an optimization of the above example, in step S43, the added Fe 3 O 4 @SiO 2 -C=C nanoparticles is 0.2 g.
[0074] Example 13: As an optimization of the above example, in step S44, the stirring time is 50 minutes to 70 minutes, the eluent is a mixed solution composed of methanol and acetic acid with a volume ratio of 9:1, wash until there is no ultraviolet and visible light adsorption at a wavelength of 264 nm in the eluent, vacuum dry at 55 °C to 65 °C, and vacuum dry for 7.5 h to 8.5 h.
[0075] Example 14: The magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen obtained by the preparation method of the magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen.
[0076] Example 15: Application of the magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen in selectively adsorbing ibuprofen.
[0077] Example 16: The magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen obtained by the preparation method of the magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen is obtained according to the following experimental steps:
[0078] S1, Preparation of Fe 3 O 4 nanoparticles:
[0079] First, dissolve 2.025 g of FeCl 3 -6H 2 O in 60 mL of ethylene glycol, add 5.50 g of NaAc (sodium acetate) and 1.50 g of PEG (polyethylene glycol), and obtain a first mixture after magnetic stirring;
[0080] Then, calcine the first mixture in a reaction kettle at 200 °C for 8 h, wash the impurities alternately with ultrapure water and ethanol, and dry it under vacuum at 60 °C for 8 h to obtain Fe 3 O 4 nanoparticles.
[0081] S2, Preparation of Fe 3 O 4 @SiO 2 :
[0082] First, disperse 0.2 g of the Fe 3 O 4 nanoparticles prepared in step S1 in a mixed solution composed of 125 mL of ethanol and ultrapure water (4:1, v / v) to obtain a first mixed solution;
[0083] Then, add 1.8 mL of NH 3 -H 2 O (ammonia water) and 0.6 mL of TEOS, and dry it under vacuum at 60 °C for 8 h to obtain Fe 3 O 4 @SiO 2 .
[0084] S3, Preparation of Fe 3 O 4 @SiO 2 -C=C nanoparticles:
[0085] First, ultrasonically disperse 200 mg of Fe3 O 4 @SiO 2 It was dispersed in a mixed solution of 120 mL of double-distilled water and acetic acid (9:1, v / v) to obtain a second mixed solution;
[0086] Then, 0.6 mL of MPS was added to the second mixed solution, and after mechanical stirring for 6 h, it was vacuum-dried at 60 °C for 8 h to obtain Fe 3 O 4 @SiO 2 -C═C nanoparticles.
[0087] S4. Preparation of MMIPs:
[0088] First, 0.1053 g of IBP was dissolved in 30 mL of methanol in a three-necked flask. 0.45 mL of APTES was added, and after mixing and stirring with a mechanical stirrer, a prepolymer was obtained;
[0089] Then, the prepolymer was stirred for 60 min to achieve complete prepolymerization, and then 1 mL of NH 3 -H 2 O and 3.75 mL of TEOS were added and stirred for 30 min to obtain a second mixture;
[0090] Next, 200 mg of Fe 3 O 4 @SiO 2 -C═C nanoparticles prepared in step S3 were added and ultrasonically dispersed to obtain a third mixture;
[0091] Finally, the third mixture was stirred for 1 h, washed with an eluent mixture of methanol and acetic acid (9:1, v / v) until there was no visible ultraviolet adsorption at a wavelength of 264 nm in the eluent, and then dried at 60 °C for 8 h to obtain MMIPs.
[0092] Example 17: Magnetic non-molecularly imprinted polymers without IBP (hereinafter referred to as MNIPs for short) were obtained according to the following experimental steps:
[0093] Fe 3 O 4 The preparation of nanoparticles, the preparation of Fe 3 O 4 @SiO 2 The preparation of, and the preparation of Fe 3 O 4 @SiO 2 -C═C nanoparticles were all the same as the method in Example 12, except for the preparation of MNIPs.
[0094] The specific process of preparing MNIPs is as follows:
[0095] First, 0.45 mL of APTES was dissolved in 30 mL of methanol, 1 mL of NH 3 -H 2 O and 3.75 mL of TEOS were added and stirred for 30 minutes;
[0096] Then, 200 mg of Fe 3 O 4 @SiO 2 -C═C nanoparticles prepared in step S3 were added and ultrasonically dispersed to obtain a third mixture;
[0097] Finally, the third mixture was stirred for 1 h and dried at 60 °C for 8 h to obtain MNIPs.
[0098] The structure of the MMIPs prepared in Example 16 was comprehensively characterized, and the adsorption performances of MMIPs and MNIPs (prepared in Example 17) were evaluated and compared by adsorption isotherms, adsorption kinetics and selective adsorption. In addition, MMIPs were used as solid-phase extraction (SPE) packing materials to concentrate and detect IBP in water, and the process was as follows:
[0099] 1. Adsorption experiment
[0100] 1.1 Isothermal adsorption experiment
[0101] Six portions of 10 mg of IBP-MMIPs and MNIPs were weighed into 10 mL glass bottles. 10.0 mL of ibuprofen-methanol solutions with concentrations of 100 mg / L - 800 mg / L were added successively. They were oscillated at 25 °C for 150 min. After standing and precipitation, the supernatant was filtered through a 0.22 μm Teflon filter head and the absorbance was measured. The absorbance of the solution at 264 nm was recorded, and the adsorption kinetic curve was plotted. The results were as Figure 1 shown. Figure 1 In, A is the adsorption isotherm diagram of MMIPs and MNIPs; B is the Langmuir fitting curve diagram; C is the Freundlich fitting curve diagram; D is the adsorption kinetic curve diagram of MMIPs and MNIPs; E is the pseudo-first-order model diagram; F is the pseudo-second-order model diagram.
[0102] The adsorption capacity was calculated according to the following formula:
[0103] Q = (C 0 - C t )V / m
[0104] where Q is the adsorption capacity, mg / g; C 0 and C t are the initial concentration and equilibrium concentration of IBP in the aqueous solution, respectively, mg / L -1; m is the mass of the polymer used, in mg; V represents the volume of the solution, in mL.
[0105] 1.2 Adsorption Kinetics Experiment
[0106] Weigh 6 portions of 10 mg of MMIPs, and add 5.0 mL of 500 mg / L ibuprofen-methanol solution to each portion. Oscillate them for 30 min, 60 min, 90 min, 120 min, and 150 min respectively. After standing for precipitation, filter the supernatant with a 0.22 μm Teflon filter head and measure the absorbance. Record the absorbance of the solution at 264 nm and plot the adsorption kinetics curve. The results are as Figure 1 shown.
[0107] Calculate the adsorption capacity according to the following formula:
[0108] Q = (C 0 - C t )V / m
[0109] where Q is the adsorption capacity, in mg / g; C 0 and C t are the initial concentration and equilibrium concentration of IBP in the aqueous solution, in mg / L -1 ; m is the mass of the polymer used, in mg; V represents the volume of the solution, in mL.
[0110] 1.3 Selectivity Experiment
[0111] Weigh 3 portions of 10 mg of IBP-MMIPs, and add 5.0 mL of methanol solutions of ibuprofen (IBP), salicylic acid, and clofibric acid with a concentration of 500 mg / L to each portion. Oscillate them for 150 min. Filter with a 0.22 μm Teflon filter head, measure the absorbance of the three structural analogs in the solution, calculate the adsorption capacity, and calculate the imprinting factor.
[0112] Calculate the imprinting factor according to the following formula:
[0113] IF = Q MMIPs / Q MNIPs
[0114] where IF is the imprinting factor, dimensionless, and it is an index to measure the imprinting ability of MMIPs relative to MNIPs; Q MMIPs is the adsorption capacity of MMIPs, in mg / g; Q MNIPs is the adsorption capacity of MNIPs, in mg / g.
[0115] 2. Solid Phase Extraction
[0116] The MSPE column was prepared by the improved wet packing method. 100 mg of dried MMIPs were loaded into an empty SPE column that had been thoroughly dried and equipped with frits at the bottom and top. Before each experiment, the polymer was rinsed with 5.0 mL of distilled water and 5.0 mL of methanol. Then, the sample was prepared using the IBP solution. The sample volume (V sample volume = 0.5, 1.0, 2.0, 3.0, 4.0, 5.0 mL) and the elution volume (V elution volume = 1.0, 2.0, 3.0, 4.0, 5.0 mL) were optimized. Finally, the eluate was collected and its efficiency was verified by HPLC analysis.
[0117] 3. Results and Discussion
[0118] 3.1 Isothermal Adsorption
[0119] The static adsorption capacities of MMIPs and MNIPs in the range of 100 mg / L to 800 mg / L were measured, and the results are as Figure 1 shown. As can be seen from Figure 1 a, when the initial concentration was lower than 500 mg / L, the adsorption amount of MMIPs gradually increased, and when the IBP concentration was 800 mg / L, the adsorption amount of MMIPs reached the peak. Obviously, the calculated adsorption capacity of MMIPs for 500 mg / L IBP - methanol was 68.18 mg / g, which was about 1.70 times higher than that of MNIPs (40.01 mg / g). These results indicate that they are related to the specific adsorption properties of MMIPs. This proves that hydrogen bonds are formed between IBP and APTES, and good imprinting sites appear on the molecular imprinting layer.
[0120] Among them, Table 1 lists the isothermal adsorption related parameters of MMIPs and MNIPs.
[0121] Table 1
[0122]
[0123] As can be seen from Table 1, compared with the Langmuir model, the correlation coefficient (R 2 = 0.9850) of the Freundlich model is greater than that of the Langmuir model (R 2 = 0.9725). These results in Table 1 indicate that multilayer adsorption occurred during the adsorption process of MMIPs and MNIPs, and there was diversity in the adsorption sites on the surface of the nanoparticles.
[0124] 3.2 Dynamic Adsorption
[0125] From Figure 1It can be seen that the adsorption kinetics experiment evaluated the adsorption efficiency of MMIPs and MNIPs. Before 30 min, the adsorption amounts of MMIPs and MNIPs increased rapidly. After 90 min, the adsorption amounts of MMIPs and MNIPs gradually decreased until equilibrium was reached. This is because a large number of binding sites of MMIPs are located on the surface of MMIPs, reducing the mass transfer resistance and making it easy for IBP to enter the recognition sites.
[0126] To further study the adsorption kinetics, two kinetic models were fitted using the pseudo-first-order equation and the pseudo-second-order equation, and the relevant parameters are shown in Table 2.
[0127] Table 2
[0128]
[0129] As can be seen from Table 2, (R 2 = 9834) is higher than that of the pseudo-first-order kinetic model (R 2 = 0.9605), and the maximum adsorption capacity obtained from the experiment (Q e = 68.18 mg / g) is close to the Q e = 91.16 mg / g value given by the pseudo-second-order kinetic model. Therefore, the adsorption process better conforms to the pseudo-second-order equation, indicating that the adsorption of IBP by MMIPs is mainly chemical adsorption.
[0130] 3.3 Selectivity experiment
[0131] The selective recognition characteristics of MMIPs were studied, and the results are as Figure 2 shown. The adsorption capacities of MMIPs for IBP, CA, and SA are 68.18, 48.36, and 50.17 mg / g, respectively, because there are a large number of recognition cavities compatible with IBP on the surface of MMIPs. The IF was calculated using the following formula.
[0132] IF = Q MMIPs / Q MNIPs
[0133] where IF is the imprinting factor, dimensionless, and it is an index to measure the imprinting ability of MMIPs relative to MNIPs; Q MMIPs is the adsorption capacity of MMIPs, mg / g; Q MNIPs is the adsorption capacity of MNIPs, mg / g.
[0134] The IF values of IBP, CA, and SA are 1.70, 1.08, and 1.15, respectively, further proving that MMIPs have good specific adsorption for IBP. At the same time, due to the lack of imprinted cavities on the surface of MNIPs, the adsorption capacities of MNIPs for these analogues are not very different. It can be seen that MMIPs have the highest adsorption capacity and selectivity for IBP.
[0135] In summary, the present invention uses Fe 3 O 4 @SiO 2 -C=C nanoparticles as carriers, IBP as template molecules, APTES as functional monomers, and TEOS as cross-linking agents to prepare magnetic molecularly imprinted polymers for adsorbing IBP. Its structure was comprehensively characterized, and its adsorption performance was evaluated by adsorption isotherms, adsorption kinetics, and selective adsorption. The results show that the magnetic molecularly imprinted polymer is an effective adsorbent for removing and detecting IBP in water.
[0136] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effects. Non-essential technical features can be added or subtracted according to actual needs to meet the requirements of different situations.
Claims
1. A method for preparing a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen, characterized in that Follow the steps below: S1, Fe3O4 nanoparticles are prepared; S2, Fe3O4@SiO2 was prepared; S3, Fe3O4@SiO2-C=C nanoparticles were prepared; S4, using IBP as a template molecule, APTES as a functional monomer, and TEOS as a cross-linking agent, a magnetic molecular imprinting polymer for selective adsorption of ibuprofen was prepared.
2. The method for preparing a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen according to claim 1, characterized in that: In step S1, the specific process of preparing Fe3O4 nanoparticles includes: S11, dissolving a required amount of FeCl3-6H2O in ethylene glycol, then adding a required amount of NaAc and PEG, and stirring to obtain a first mixture, wherein 2.025 g of FeCl3-6H2O is dissolved in every 60 mL of ethylene glycol, and 5.50 g of NaAc and 1.50 g of PEG are added to every 2.025 g of FeCl3-6H2O; S12, calcining the first mixture, washing the impurities of the obtained product with ultrapure water and ethanol alternately, and then vacuum drying to obtain Fe3O4 nanoparticles, wherein the calcination temperature is 180°C to 220°C, the calcination time is 7.5h to 8.5h, the vacuum drying temperature is 55°C to 65°C, and the vacuum drying time is 7.5h to 8.5h.
3. The method for preparing a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen according to claim 1 or 2, characterized in that In step S2, the specific process of preparing Fe3O4@SiO2 includes: S21, dispersing the required amount of Fe3O4 nanoparticles prepared in step S1 in a mixed solution of ethanol and ultrapure water to obtain a first mixed solution; S22, adding required amounts of ammonia water and TEOS to the first mixed solution, mixing and vacuum drying to obtain Fe3O4@SiO2.
4. The method for preparing a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen according to claim 3, characterized in that In step S21, 0.2 g of Fe3O4 nanoparticles are dispersed in every 125 mL of the mixed solution, wherein the volume ratio of ethanol to ultrapure water in the mixed solution is 4:1; or / and, in step S22, 1.8 mL of ammonia water and 0.6 mL of LTEOS are added to every 0.2 g of Fe3O4 nanoparticles, the vacuum drying temperature is 55°C to 65°C, and the vacuum drying time is 7.5 h to 8.5 h.
5. The method for preparing a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen according to any one of claims 1 to 4, characterized in that In step S3, the specific process of preparing Fe3O4@SiO2-C=C nanoparticles includes: S31, dispersing the required amount of Fe3O4@SiO2 prepared in step S2 in a mixed solution of double distilled water and acetic acid to obtain a second mixed solution; S32, adding a required amount of MPS to the second mixed solution, mixing and stirring evenly, and then vacuum drying to obtain Fe3O4@SiO2-C=C nanoparticles.
6. The method for preparing a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen according to claim 5, characterized in that In step S31, 0.2 g of Fe3O4@SiO2 is dispersed in every 120 mL of the mixed solution, wherein the volume ratio of double distilled water to acetic acid in the mixed solution is 9:1; or / and, in step S32, 0.6 mL of MPS is added to every 0.2 g of Fe3O4@SiO2, the stirring time is 5.5 h to 6.5 h, the vacuum drying temperature is 55°C to 65°C, and the vacuum drying time is 7.5 h to 8.5 h.
7. The method for preparing a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen according to any one of claims 1 to 6, characterized in that In step S4, the specific process of preparing the magnetic molecular imprinted polymer for selectively adsorbing ibuprofen includes: S41, dissolving a required amount of IBP in methanol, adding functional monomer APTES, mixing and stirring to obtain a prepolymer; S42, adding a required amount of ammonia water and a crosslinking agent TEOS to the prepolymer, mixing and stirring to obtain a second mixture; S43, adding the required amount of Fe3O4@SiO2-C=C nanoparticles prepared in step S3 to the second mixture, and dispersing by ultrasonic to obtain a third mixture; S44, stirring the third mixture, washing it with an eluent, and then vacuum drying it to obtain a magnetic molecular imprinting polymer for selectively adsorbing ibuprofen.
8. The method for preparing a magnetic molecularly imprinted polymer for selectively adsorbing ibuprofen according to claim 7, characterized in that In step S41, 0.1053 g of IBP is dissolved in every 30 mL of methanol, and 0.45 mL of APTES is added to every 0.1053 g of IBP; or / and, in step S42, 1 mL of ammonia water and 3.75 mL of LTEOS are mixed, and the stirring time is 20 to 40 minutes; or / and, in step S43, 0.2 g of Fe3O4@SiO2-C=C nanoparticles are added; or / and, in step S44, the stirring time is 50 to 70 minutes, the eluent is a mixture of methanol and acetic acid in a volume ratio of 9:1, and the eluent is washed until there is no ultraviolet visible light adsorption at a wavelength of 264 nm in the eluent, the vacuum drying temperature is 55°C to 65°C, and the vacuum drying time is 7.5h to 8.5h.
9. A magnetic molecular imprinted polymer for selectively adsorbing ibuprofen obtained according to the preparation method according to any one of claims 1 to 8.
10. Use of the magnetic molecular imprinted polymer for selective adsorption of ibuprofen according to claim 9 in selective adsorption of ibuprofen.